(untitled) (Research, Society and Development, 2021)
Anxiety is among the psychiatric disorders often found in students, associated with learning difficulties and reduced academic performance. Since the professional future depends on good intellectual development, these individuals benefit from a damage free intervention that reduces the symptoms of the anxious condition proposed by Flower Therapy. The aim of this study was to investigate anxiety score and classifications in students undergoing flower therapy through a randomized, double-blind clinical trial. The study sample consisted of physiotherapy students from the Western Paraná State University, from both genders, aged between 18 and 30 years old. The anxiety level (score and classification) was assessed according to Trait Anxiety Inventory (STAI-T). The sample consisted of 62 students who obtained medium and high anxiety level. This sample was divided into three groups: treatment group (TG), placebo group (PG) and control group (CG). The TG used Minas System Examination Formula (Basilicum, Foeniculum, Lavandula, Momordica, Rosmarinus, Sonchus and Tabebuia); the PG used preservative water, and the CG only answered the questionnaire before and after thirty days. Difference in the questionnaire classification was observed between TG and CG. In pre and post intervention analysis, TG showed a reduction in the score and in the questionnaire classification. GP showed statistical difference in the questionnaire score, and CG did not present significant differences. The use of the Flower Formula and the placebo compound were effective in reducing anxiety symptoms. The Flower Formula, had a better response than the placebo compound as it exhibited a greater reduction in score and classification.